Housing market convergence: Evidence from Germany - Umut Unal; Bernd Hayo; Isil Erol (Philipps-University Marburg, School of Business and Economics, 2022)
This paper provides an analysis of the convergence pattern of German housing prices and rents employing a new dataset that covers all the country's administrative districts. In addition to conventional tests for β-convergence and δ-convergence, we apply Phillips and Sul's (2007) approach so as to allow for the various heterogeneity and transitional dynamics across districts. Our results reveal no evidence of convergence across Germany or within states; rather, we discover widespread evidence of divergence, as well as evidence of inter-state convergence and support for the existence of convergence clubs. At the federal level, we identify club numbers ranging from 11 (for existing flat prices) to 5 (for new flat rents). At the state level, the estimated number of clubs is generally lower, ranging from 0 to 6.
Keywords: R10; R30; R31; 330; Convergence; Germany; Housing prices; district-level data; convergence clubs